Muzakki’s Trust In Zakat Payment: The Role Of Zakat Literacy, Transparency, Accountability, And Religiosity - Adiwijaya, Zainal Alim; Pratiwi, Arimbi Desya; Rosalina, Rita (LPPM ISNJ Bengkalis, 2024)
This study aims to analyze the influence of zakat literacy, transparency, accountability, and religiosity on Muzakki's trust in paying zakat at the zakat amil institution. This research uses an explanatory research type with a quantitative approach that uses primary data through data collection in questionnaires. The population in this study was the Muzakki at LAZIZMU Central Java, Indonesia. The sample was randomly selected, and 50 Muzakki samples were obtained. The results of this study indicate that zakat literacy and accountability positively affect Muzakki's trust in paying for zakat. In contrast, transparency and religiosity negatively affect Muzakki's trust in paying zakat. This study provides theoretical implications that can complement existing theories and become a source of literacy and reference for further research. Then, it can provide comprehensive insight into how zakat institutions perform, thus encouraging the intention and behavior of paying zakat in real terms in the community. Practical implications include providing an overview of zakat management institutions in increasing public trust in paying zakat.